Pengaruh Program Insentif dan Pelatihan Kerja terhadap Kinerja Karyawan - Sri Sulistyowati (JMK (Jurnal Manajemen dan Kewirausahaan), 2018)
This Research to know and analyse employees performance in Terra of Computer System Kediri. Variable in this research is incentive and training of job/activity as variable of X, and employees performance as variable Y. Research method the used is technique method analyse descriptive data. While sampel in this research that is employees of Terra Computer System Kediri amounting to 25 people. How employees can work with as good as possible in finishing work with existence of gift/ giving of incentive and training of job/activity. This research aim to to show influence of incentive and training of job/activity to employees performance. In analysing data used by validity test, test reliabilitas, doubled linear regression analysis, test of F, test T, and test of determinasi. In this research show R niai equal to 0,645 with the meaning relation or correlation between independent variable consisting of incentive ( X1), training of job ( X2) with variable of dependen employees performance ( Y) have high relation or very strong. Assess R Square show 0,416, this means that influence of independent variable consisting of incentive ( X1), training of job ( X2) to variable of dependen employees performance ( Y) is 41,6% while 58,4% influenced by other factor.